(untitled) (Contemporary Mathematics, 2025)
Balancing work-life challenges in pressured careers such as surgery can only be done with due consideration, bearing in mind that work-life conflict is inevitable and demands some strategies capable of addressing reasons related to preference and the rationality often associated with complex scenarios. So, these challenges require a robust framework that offers reliable and actionable insights. The contribution of this research is in developing a novel approach, known as the Circular Pythagorean Fuzzy Set Weighted Aggregated Sum Product Assessment (C-PyFS-WASPAS), that can be implemented to assess the performance of the alternative in the environment that is characterized by vagueness and imprecision. This framework integrates the advantages of the Weighted Aggregated Sum Product Assessment (WASPAS) method with flexibility in the Circular Pythagorean Fuzzy Set (C-PyFS) to address imprecision and subjective preference in decision-making. To show its viability, the proposed approach evaluates options regarding work-life balance for surgeons based on essential options such as adequate sleep, time management, goal congruence sessions, and work-life balance measures. The results show that the C-PyFS-WASPAS method provides better-understood results than previous methods and can provide significant information to decision-makers. Moreover, a sensitive analysis is conducted by varying the weight values, highlighting its performance towards stability. A comparison analysis has been performed to show its effectiveness, demonstrating that the proposed approach is more accurate than others. This framework has much potential in terms of real-world applications, and future research will build upon these concepts and adapt this approach to functioning in dynamic environments, as well as incorporate additional high-level computational methods for the benefit of a more extensive range of applications.